Students’ Ability in Writing Sequence of Events Based on Up Movie - Khairunnisa , Fitriyany; Wahyuni, Sri; Etfita, Fauzul; Asnawi, Asnawi (JEE (Journal of English Education), 2021)
This research was conducted aiming to an analysis of students’ ability in writing sequence of events based on “UP” movie by the third-year students at English Language Education Study Program of Universitas Islam Riau. This study was descriptive research and the method used in this research is the quantitative method with utilizing SPSS software to calculate the frequency, percentage, and mean score. The subject of this research were the students at the third year that consisted of 35 students and this research focused on five aspects of writing. In gathering the data, this research used Google form to collect the result writing test of the students. From the data analysis of 35 students who took the writing test, 4 students were in good to excellent level which the percentage is 11.4%. 27 students were in average to good level which the percentage is 77.1%. 4 students gain poor to average level with the percentage is 11.4% and no one of the students (0%) got poor level. Based on the researcher analysis from the result of the research, the highest score that most students could gain was in the vocabulary aspect with the mean score 3.68. Meanwhile, the lowest score that the students could gain was in fluency with the mean score 3.06. So, in this case, the researcher could interpret that the third-year students were on average to good level and able to write the sequence of events of the movie.